PENERAPAN TEKNOLOGI TEPAT GUNA PADA PELAKU PERIKANAN KOTA MEDAN - Catur Pramono Adi (JURNAL KASTARA, 2023)
In order for the technology that will be the technical guidance material according to the needs, the selection of materials is determined through focus group discussions (FGD) attended by stakeholders in the area that will be the location of the activity implementation. The FGD participants were given a list of recommended technologies and asked to choose a technology based on 7 (seven) criteria for the effectiveness of the technology. The technology chosen with the highest number is chosen to be the material for technical guidance. The specific objective is to utilize science and technology resulting from research and development by extension agents and the public so that they can improve the quality and competence of extension officers and key actors in fisheries so that they have a work ethic that is productive, skilled, creative, disciplined, professional and able to utilize, develop and master innovative technologies. The second specific objective is to increase the number of partner networks for the utilization of science and technology with the spread of science and technology so that BRSDM will receive feedback and requests for the dissemination of technologies that have been found so as to accelerate the dissemination and utilization of science and technology from research and development results to the public. Based on presentations, discussions, field visits, and evaluations of increasing participants' knowledge of technology as material for technology guidance, several conclusions can be formulated: a). Based on the enthusiasm and response, the participants considered that this activity was very useful for the addition of knowledge and knowledge, especially technology which was the subject of technical guidance, to become a provision for carrying out daily field assignments; b). The increase in participants' knowledge varied between individual participants. This is of course related to the various educational and occupational backgrounds of the participants (there are capture fisheries, there are aquaculture) in accordance with the fisheries potential in their working areas and the material also varies.